Ion beam emittance measurement based on transformation matrix theory - Tongnopparat N. (2014)
In order to develop a high-quality ion beam line for bioengineering research and applications, the ion beam emittance of a beam line was measured to provide information on designing the following beam optics to meet the ion beam's bioengineering requirements. The measurement was based on the transformation matrix theory for electrostatic and magnetic devices. The experimental setup included an ion source, an Einzel lens, a self-developed quadrupole magnetic lens and a multi-wire beam profile monitor. In the measurement, the beam size was first measured at the beam profile monitor as a function of focusing and was then fitted to the transformation matrix parameters. Finally, the best-fitted parameters were used to construct the phase ellipse of the beam's emittance. The details on the relevant theory and measurement are described and the results are presented.